Galectins as pivotal components in oncogenesis and immune exclusion in human malignancies - Kapetanakis, Nikiforos-Ioannis; Busson, Pierre (Frontiers in Immunology, 2023)
Galectins are galactoside-binding proteins, exerting numerous functions inside and outside the cell, particularly conferring adaptation to stress factors. For most of them, aberrant expression profiles have been reported in the context of cancer. Albeit not being oncogenic drivers, galectins can be harnessed to exacerbate the malignant phenotype. Their impact on disease establishment and progression is not limited to making cancer cells resistant to apoptosis, but is prominent in the context of the tumor microenvironment, where it fosters angiogenesis, immune escape and exclusion. This review focuses mainly on Gal-1, Gal-3 and Gal-9 for which the involvement in cancer biology is best known. It presents the types of galectin dysregulations, attempts to explain the mechanisms behind them and analyzes the different ways in which they favor tumour growth. In an era where tumour resistance to immunotherapy appears as a major challenge, we highlight the crucial immunosuppressive roles of galectins and the potential therapeutic benefits of combinatorial approaches including galectin inhibition.